2016
DOI: 10.5999/aps.2016.43.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Photogrammetric Analysis of Attractiveness in Indian Faces

Abstract: BackgroundThe objective of this study was to assess the attractive facial features of the Indian population. We tried to evaluate subjective ratings of facial attractiveness and identify which facial aesthetic subunits were important for facial attractiveness.MethodsA cross-sectional study was conducted of 150 samples (referred to as candidates). Frontal photographs were analyzed. An orthodontist, a prosthodontist, an oral surgeon, a dentist, an artist, a photographer and two laymen (estimators) subjectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A very narrow face in males and a narrow face in females (average facial index value 96.02 and 91.62, respectively) were most often evaluated with high marks in our study. With the average facial index value of 98.33 in males and 94.81 in females, very narrow and narrow faces were also rated higher in a study based on an Indian population (Duggal et al, ). By the same selection of the most attractive shapes of face, the participants of the Serbian and Indian populations show that for some facial characteristics, there might be universal traits of beauty.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A very narrow face in males and a narrow face in females (average facial index value 96.02 and 91.62, respectively) were most often evaluated with high marks in our study. With the average facial index value of 98.33 in males and 94.81 in females, very narrow and narrow faces were also rated higher in a study based on an Indian population (Duggal et al, ). By the same selection of the most attractive shapes of face, the participants of the Serbian and Indian populations show that for some facial characteristics, there might be universal traits of beauty.…”
Section: Discussionmentioning
confidence: 94%
“…By analyzing the nasal index of the highest rated noses, we found that the nose with a medium width was the most desirable for both sexes, with an average nasal index value of 71.74 in males and 72.69 in females. Examination of the dimensions of the nose in perceived attractive individuals was performed in India (Duggal et al, ). This study found that wider noses in both sexes were the most desirable, with an average nasal index of 98.18 in males and 98.10 in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…- The first and the second questions lead us to think, just like Perret did (20), that not everyone has the same criteria for the same picture, but if we add the statements "very good looking", "good looking" and "normal", the resulting "normality" interval stands for 90.07% of the answers, which is why we can state that, like Duggal (2016) (6), that there is a "facial normality".…”
Section: Analysis Of Main Componentsmentioning
confidence: 87%
“…This was contrary to findings of other studies conducted on Indian population for lateral cephalograms. [22][23][24] Although photographs assume equal importance as essential diagnostic aids, radiographic or anthropometric analysis cannot be replaced with photographs.…”
Section: Future Implications and Scope For Additional Researchmentioning
confidence: 99%